TRANSFORMASI DIGITAL ADMINISTRASI DESA Pendampingan Aparat Desa Wasilomata 1 Dalam Optimalisasi Google Sites Untuk Pelayanan Publik - Achmad, Farid Yusuf Nur; Ananto, Muh. Aldi Musbaq; Arham, La Ode Muhammad (MAJU : Indonesian Journal of Community Empowerment, 2025)
The manual administration and public services in Wasilomata Village face numerous challenges, including difficulties in document management and limited community access to important information and village services. These issues result in inefficiencies in public services and a lack of transparency in information dissemination. Therefore, the digitalization of administration through the development of a village website based on Google Sites is expected to be a solution to these problems. This community service project aims to design and build a village website that serves as a digital platform for administrative management and public service delivery. The implementation methods include identifying the village's needs, designing and developing the website, and providing training for village officials to manage and update information independently. The website is equipped with key features such as village information, online service forms, announcements, and a complaints channel. The results of the project show that the website successfully helped the village government manage information more efficiently and improved residents' access to public services. The training provided also enabled village officials to operate and update the website autonomously. Thus, the digitalization of administration and public services through this website proves to be an effective and sustainable solution for Wasilomata Village.